Health status and healthcare trajectory of vulnerable asylum seekers hosted in a French Reception Center. Issue 46 (March 2022) - Cortier, Marie; de La Porte, Clémentine; Papot, Emmanuelle; Goudjo, Abdon; Guenneau, Laure; Riou, Françoise; Cervantes-Gonzalez, Minerva; Prioux, Maëlle; Yazdanpanah, Yazdan; Galy, Adrien
Abstract: Background: Europe lacks studies related to asylum-seekers' health. Methods: We described the health status, healthcare and follow-up of men seeking asylum, accommodated in a primary reception center in Paris (CPA). This observational study included volunteer patients presenting for care at the CPA primary care unit (PCU) from January to March 2018. They could be referred to on-site GPs and psychiatrists or to surrounding healthcare facilities. After their asylum application, patients were transferred to other French accommodation centers. PCU healthcare professionals could make referrals for close medical reassessments after transfer. Results: The 728 included men came mostly from Central Asia or Middle East (65%) and Africa (34%). Seventy percent reported violence during migration. Seventy-five percent (547/728) were referred to on-site GPs, 20% to psychiatrists. During patients' stay at CPA, 67% (144/214) of referrals to surrounding healthcare facilities led to performed consultations. Seven percent of all the included patients (49/728) were referred for frequent communicable infectious diseases screening. Final diagnoses (n = 1108) included 31% infectious diseases and 7% psychiatric disorders. When post-transfer accommodation centers could be reached, 69% (33/48) of the medical referrals had led to a scheduled appointment. Conclusions: The healthcare trajectory at CPA could benefit from optimization of infectious and psychiatric screenings, and improved coordination of care and follow-up. Highlights: Vulnerable migrants applying for asylum had a high rate of care seeking at the PCU. The PCU offered efficient primary care with interprets, nurses, GP and psychiatrists. Referrals could be made to healthcare facilities for additional tests or treatments. Infectious and psychiatric diseases screenings remained limited to few patients. Care continuity between PCU and places of referrals or transfer should be optimized.